Fast sediment underplating and essentially coeval juvenile magmatism in the Ordovician margin of Gondwana, Western Sierras Pampeanas, Argentina - Casquet, César (2012)
Metasedimentary high-pressure upper amphibolite facies gneisses (1.2 ± 0.1. GPa and 780 ± 45 °C) at Las Chacras, Sierra de Valle Fértil, are tectonically juxtaposed to the westernmost parts (outboard) of the Famatinian (Early Ordovician) magmatic arc, which underwent syn-plutonic middle crust high-grade metamorphism at lower pressure. U-Pb SHRIMP zircon data suggest that the gneisses contain Famatinian igneous detritus, so that their sedimentary protoliths were probably deposited in a forearc basin and then rapidly underthrust and accreted to the lower crust of the arc, essentially coevally with arc magmatism at 468 ± 4. Ma. Chemically and isotopically juvenile garnetiferous amphibolites within the gneisses are recognised as representing the most primitive magmas so far observed in this belt, which has often been considered to be a continental arc derived from isotopically mature sources. This is consistent with the idea that at least part of the dominant Famatinian magmatism originated in depleted mantle but was heavily contaminated by crustal components. © 2012 International Association for Gondwana Research.